Entrepreneurship for rural start-ups: lessons and guidance for new venture creation - Jimenez-Marin, Gloria, 1980- (New York, NY: Routledge, 2021)
'Entrepreneurs who start out with no network, no money, no market and scarce resources find a big contrast between what they read in books and the success stories from the Valley and their reality, specially first-timers. Most entrepreneurial books focus on the Business Canvas Model, simplifying the process of building a start-up. Many entrepreneurs who have no previous business experience embrace quick and lean methods without the foundations needed to build solid value proposals. This book stands out because it deals with entrepreneurship in environments far removed from large cities with fewer infrastructures, connections and resources but which also need companies that provide services to citizens and society. This book focuses on the basics, treating each part of the business canvas as a discipline itself that must be mastered. The book illustrates key lessons learned and offers guidance on essential topics for new venture success in mainstream markets. It expands critical lessons learned and points of guidance across several key topics for new venture creation. Noteworthy is the role of context, financial understanding, building business development skills and start-up communications. Entrepreneurship for Rural Start-ups will be of interest to students, academics and researchers in the field of entrepreneurship, and will be of use to individuals looking to start a local business to take advantage of the rural environment and the possibilities it offers'--
Includes bibliographical references and index.
Keywords: Entrepreneurship; New business enterprises; Rural industries